(untitled) (REMUNOM, 2025)
Teaching complex concepts in Physics, such as radioactive decay, can be challenging for students. In this context, the use of educational games is an effective tool to make learning more dynamic and accessible. This paper presents "Decay", a card game developed to assist in teaching radioactive decay. Inspired by the game Uno, "Decay" uses playful mechanics to represent fundamental concepts of radioactivity, allowing players to understand, in an interactive way, processes such as alpha, beta and gamma decay. The game was developed with accessible materials and a design thought to facilitate its application in educational environments. The proposal aims to stimulate students’ strategic reasoning and provide meaningful learning, making the assimilation of content more engaging.